Tourist Behavior An Experiential Perspective (Tourism, Hospitality & Event Management,, 2018)
This book examines and analyzes tourism consumption and tourist experiences, employing a systematic and case study-driven perspective. Covering approaches with a wider geographical background, it considers issues like tourism place experience and co-creation, as well as the behavior of tourists on guided tours, at trade shows and exhibitions, and in museums. Dedicated chapters deal with the aspect of customer satisfaction in places such as hotels or restaurants. In closing, the book highlights tourist behavior in the context of cultural heritage, regional and cultural differences and the general frameworks of consumer happiness and responsibility. Given its focus, the book provides a unique view on the interplay of tourism consumption and tourist experiences, and presents a comprehensive selection of case studies to exemplify and discuss in detail the frameworks covered and the current state of practice.